Ovarian ultrastructure in virgin queens of Apis mellifera L. narcotized by CO2 - Berger, Bruno [UNESP]; da Cruz-Landim, Carminda [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Ovaries of newly emerged virgin queens, aged 1, 3, 5, and 10 days, were submitted to an atmosphere of CO2 for 1 min, and studied by transmission electron microscopy. Newly emerged control and experimental queens were kept caged during 15 days with six nurse workers (changed every 2 days) and fed with sugar candy and water ad libitum. For the ultrastructural studies, the ovaries were collected when the queens were 3, 5, 10, and 15 days old. The effect of the treatment on the ovary was mainly evaluated by cell death incidence and acid phosphatase detection. Neither the confinement nor CO2 treatment interfered with the pattern of queen ovarian development for up to 5 days; that is, no differences were observed in ovarian ultrastructure or acid phosphatase activity between control and treated queens. Beyond the age of 10 days, treated queens showed a lower rate of cell death than controls, but the positivity to acid phosphatase reaction remained similar in both. The protective effect of CO2 on cells, however, did not persist, and 15-day-old treated queens showed no differences compared to the controls in the rates of cell death or enzyme reactivity. In conclusion, treatment with CO2 did not significantly change the ultrastructure of ovarian cells, or acid phosphatase activity in them, during the caging time of the queens. From an applied perspective, the short-term imprisonment of newly emerged queens outside of the colony, as is done by beekeepers, does not seem to affect their performance in terms of future fertility, although the narcosis, as applied in this study, may negatively affect their long-term performance. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Narcosis; Honey bee queens; Ovary development; CO2